Concomitant cervical fractures without neurological symptoms: a case report. (November 2016) - Reilly, F.; Gheiti, A.; Burke, N.; Timlin, M.
Abstract Background Non-contiguous spinal fractures are rare and most frequently occur in a fall from a height, or high energy trauma such as a road traffic accident (Reid, J Trauma 27:980–986, 1987). Cervical spine fractures tend to occur at two levels, one-third of injuries occur at the level of C2, and one-half of injuries occur at the level of C6 or at C7 (Wittenberg, Spine 27:254–257, 2002). The most devastating and fatal cervical spine injuries occur in upper cervical levels, either at craniocervical junction C1 or C2. Case report The case we present is of a young man involved in a road traffic accident in Ireland who had a concomitant non-displaced C2 vertebral body fracture and a C6–C7 fracture dislocation. The patient had no neurological symptoms. Conclusion Following concurrent ACDF at C6/7 and peg screw fixation of C2 through the same incision the patient made a full recovery.